Phase Equilibria of the Mg-Zn-Sm System in Mg-Rich Corner at 320 °C and 400 °C - Tian Yin; Zheng Ma; Hongcan Chen; Qun Luo; Jieyu Zhang; Guangxin Wu (Metals, 2022)
To clarify the controversy regarding the phase equilibria in the Mg-rich corner of the Mg-Zn-Sm system, alloys annealed at 320 °C and 400 °C were employed to determine the phase constitution, composition and crystal structure by scanning electron microscopy (SEM), X-ray diffraction (XRD) and transmission electron microscopy (TEM). The maximum solubility of Zn in Mg3Sm was measured to be 49.2 at.% at 400 °C. The Y phase (Mg62Zn31Sm7), only observed in the as-cast alloys, was determined to have an orthorhombic structure with lattice parameters of a = 10.20 Å, b = 11.26 Å and c = 9.64 Å by TEM. The hexagonal compound μ7, identified with lattice parameters of a = 34.62 Å and c = 8.94 Å, was detected during the transformation of the Y phase to the Z phase in the alloys located in the (Mg) + Mg3Sm + Z three-phase region. The phase equilibria (Mg) + Mg41Sm5 + Mg3Sm, Mg + Mg3Sm + Z, (Mg) + Z + liquid and Mg2Zn3 + Z + liquid at 400 °C are confirmed, and the three-phase region (Mg) + Z + MgZn exists in the Mg-Zn side at 320 °C. Subsequently, a self-consistent thermodynamic description was obtained based on the experimental data. Meanwhile, solidification simulation of Y phase formation was conducted by suppressing the stale Z phase, which can reasonably explain the as-cast microstructure of alloys in the Mg-rich corner. The thermodynamic database would be helpful for the further development of Mg-Zn-Sm alloys.